[OP.6B.01] DIRECT ESTIMATION OF CENTRAL SYSTOLIC PRESSURE FROM PERIPHERAL PRESSURES: A PROOF OF CONCEPT BASED ON THE META-ANALYSIS OF HIGH-FIDELITY PRESSURE STUDIES. (September 2016) - Chemla, D.; Millasseau, S.; Lau, E.M.T.; Attal, P.; Nittenberg, A.
Abstract : Objective: The amplification of systolic pressure from aorta to the brachial artery depends on many factors including age, gender, patient's height, heart rate and arterial stiffness. Non-invasive estimation of central pressure usually requires a transfer function and/or the morphological analysis of peripheral pressure waveforms (e.g., as obtained by using arterial tonometry). We have developed a new method (DCBP) to estimate central systolic blood pressure (cSBP) directly from peripheral pressure values. Design and method: The accuracy of the DCBP method was tested in the present meta-analysis in which only invasive studies with high fidelity pressure recordings at both the central aortic level and brachial level were included. Results: Five studies fulfilled the inclusion criteria with a total of 282 subjects (77.3% male). All measurements were obtained during diagnostic cardiac catheterization for suspected coronary artery disease (CAD). Mean age ± SD was 63.3 ± 13.2 years, heart rate was 67.1 ± 11.3 bpm and high fidelity invasive brachial pressures were 137.9 ± 19.9 mmHg, 70.9 ± 10.2 mmHg and 97.1 ± 11.7 mmHg for systolic, diastolic and mean pressures respectively. The measured invasive cSBP was 131.1 ± 19.9 mmHg (amplification of systolic pressure = 6.8 mmHg). The mean cSBP estimated by the DCBP method was 132.9 mmHg. The mean difference compared to invasive value was 1.8 mmHg (1.4%). Conclusions: This meta-analysis from invasive high-fidelity pressure data from the literature showed that our DCBP method may accurately estimate cSBP from peripheral pressure values, without the need to perform a pressure waveform analysis or to use a transfer function. The results pertained strictly to the studied population (patients aged 63.3 years on average and patients with a high suspicion of CAD). Further prospective studies are required to confirm our results and also to document the accuracy and precision of our DCBP method in various populations as well as the sensitivity of DCBP to the peripheral pressure measurement method.